PUPIL’S ACADEMIC SELF-CONCEPT AND ACHIEVEMENT IN SCIENCE : THE EFFECTS OF HOME ENVIRONMENT - Padhi, J.S. (SCHOOL SCIENCE, 2013)
Home is the social institution which has the most far reaching influence on the development of the child. It does not only provide the hereditary transmission of basic potentials for his development, but also provides environmental condition, personal relationships and cultural pattern, favourable and unfavourable, positive and negative, as reflected from its structure, socialeconomic and cultural status and the pattern of relationship and emotional state among its members (Kundu, 1977). The home also sets a pattern for the child’s attitude towards people, things and institutions